Randall D. Williams letter to Thomas H. Kent regarding a Snowy Owl sighting in Sioux City, November 26, 1987 - Williams, Randall D.et al (1987)
Letter from Randall D. Williams to Thomas H. Kent regarding a Snowy Owl sighting in Sioux City, November 26, 1987. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. This document is related to a field report contributed by Jack Jones that contains a photograph of the Snowy Owl sighting in Sioux City: https://avian.lib.iastate.edu/documents/4015/view Epson - sheet feed